Prediction of Phosphorus Concentration in an Unconfined Aquifer Using Visual Modflow - Saghravani, Seyed Reza (2009)
Groundwater as a source of water for municipal, industrial, and agricultural purposes plays a key role in many societies around the world and should be safeguarded against pollution. Nutrients such as phosphorus can be transported to other places by groundwater and has adverse effect on ecosystem of water bodies. Phosphorus causes turbidity in water and eutrophication in surface water and aquatic situation to terrestrial constantly. The objective of this study is to predict groundwater flow direction and spreading of phosphorus in an aquifer located at the Engineering Complex of the Universiti Putra Malaysia. Fertilizers, as main source of phosphorus were used before in study area. Also the fertilizers are currently used at an area located south of the Engineering Complex and it has an adverse effect on quality of groundwater. Visual MODFLOW, is a powerful software package, was used to predict the changes of groundwater flow patterns and concentration of phosphorus for period of 10 and 50 years respectively. These two periods were selected because adsorption and slow movement of phosphorus in groundwater usually take long time. However, mobility of phosphorus is resumed as the adsorption capacity of phosphorus in the soil is reached. Data from 11 constructed wells within the study area were collected to determine groundwater level from surface, thickness of geological formation, and concentration of phosphorus. Groundwater movement direction was determined by the triangular linear interpolation and the field data obtained from the observation wells indicate that groundwater flow is from Southeast to Northwest. The concentration of orthophosphorus, as the dominant form of phosphorus was measured in laboratory using spectrophotometer. The results show that concentrations of orthophosphorus in vicinity of the swamp are 0.64 mg/l, and 0.5 mg/l, in the pond is 0.22 mg/l, in western part of the area is 0.13 mg/l and in the center of study area is 0.31 mg/l. These concentrations of phosphorus in the study area show that the highest concentration occurs in the swamp and the concentration decreases with distance from the swamp down to the value of 0.13 mg/l. Visual MODFLOW, which include MODFLOW and MT3DMS, was employed to predict the direction of groundwater flow and concentration of phosphorus for periods of 10 and 50 years. During these periods two types of Constant Head Boundary (CHB) were used. In the first type, the CHB was placed in the northern part of the area and movement of groundwater during the prediction periods was implemented without any change in hydraulic head. The result shows that phosphorus does not flow to the pond but might be transferred out of the study area due to groundwater flow. In the second type, the CHB was located by the pond to record the fate of phosphorus whenever water depth in the pond drops two meters. The result indicates that the pollutant is directly transferred to the pond from the swamp especially via layer No.2 and this can be related to its high hydraulic conductivity. Prediction of contaminated groundwater shows that the concentration of phosphorus increases at the end of prediction period at the study area and this can be attributed to its migration from the swamp area.